Saur and decline: Patterns in lizard imports to the US (2000–2022) - Max Dolton Jones (PLoS ONE, 2025)
The United States is an important component of global wildlife trade and benefits from the recording of trade data in the US Law Enforcement Management Information System (LEMIS). Despite its limitations, studies are beginning to highlight broad trends of US wildlife trade using this dataset which warrants further, more focused, investigations into taxon-specific data available within LEMIS data. I used LEMIS data to investigate patterns in lizard imports to the US between 2000 and 2022. Over 18.8 million whole lizards, comprised of 1,002 species, 259 genera, and 39 families, were imported to the US during this recording period. Similar to overall wildlife trade trends, many of the lizards were wild-sourced (61.7%) and likely imported due to the demands from the pet trade (99.8% for commercial purposes). The majority of the importations were of lizards from three families— Gekkonidae , Agamidae , and Iguanidae —which combined made up over 66% of all imports despite constituting only 7.7% of the family diversity. Overall, there was a decline in the number of lizard imports over time, yet there was an increase in the number of species being imported; with newly imported species increasing linearly. I highlight and discuss some of the patterns and implications that the lizard import data are suggesting, such as drivers of lizard imports, invasion risk, geographic collection “hotspots”, and limitations of the LEMIS data.